Impact of COVID-19 pandemic on diabetes: a cross-sectional study at urban health centre in Goa - Gauns, Sneha Laxman; Dhupdale, Nitin Y. (International Journal Of Community Medicine And Public Health, 2022)
Background: Diabetes is an important comorbidity which is contributing to the mortality among COVID-19 patients. There are limited studies in Goa which have measured the impact of COVID-19 on the diabetes. Therefore, this study is undertaken to measure the impact of lockdown on glycaemic control in patients with T2DM. The study objectives were to assess the changes in HbA1c and to identify some factors affecting the glycaemic control during the pandemic on the urban population of Goa during the period of pandemic. Methods: A cross-sectional comparative study was undertaken during August to September 2020 amongst Diabetic patients undergoing treatment at Santa Cruz (Goa). Data was collected via oral questionnaire and from patients records at 6 months before and after lockdown after IEC approval. The data was entered into excel v2010, and analysed using SPSS v22 and expressed as simple proportion and percentages. Results: Out of total 50 patients enrolled in the study, the mean post-lockdown HbA1c (8.2±2.1) was found to be higher as compared to pre-lockdown values (7.3±1.3) and the difference was statistically significant (p<0.05). The Chi Square test was calculated comparing HbA1c after lockdown with Diet, exercise and drug compliance which was found to be statistically significant (p<0.05). Conclusions: Mean HbA1c of 50 T2DM patients was higher post lockdown. There is a need to re enforce necessary lifestyle modification and prescribed drug compliance for adequate diabetes control during COVID-19 pandemic to reduce overall morbidity.